Role of anti vascular endothelial growth factor (VEGF) in ophthalmology - Pandey, Achyut N. (International Journal of Basic & Clinical Pharmacology, 2017)
Vascular endothelial growth factor (VEGF), is a naturally occurring signal protein which is proinflammatory, stimulates angiogenesis and potent inducer of vascular permeability. Its role in normal physiology includes in embryonic development, wound healing and bone repair, neovascularization following MI and demonstrated in brain, kidney and GI mucosa. VEGF is responsible for many retinal diseases by causing new vessel growth and by increasing leakage and causing retinal swelling. Their use in ophthalmology includes in both anterior and posterior segment pathologies. This article explains the role of VEGFs, their mechanism of action, anti VEGFs, classification, their use, various studies and other aspects.